The Confucian Filial Duty to Care for Elderly Parents - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 2008)
A central feature of Confucianism is the doctrine that an adult child has, for want of a better word, the ‘duty’ to care for his elderly parents1. Whether this doctrine should be framed in terms of an ethic of duties as opposed to an ethic of virtues is a vexed question. It might be argued that the doctrine is best framed in terms of the behaviour and dispositions appropriate to an agent who is, within the Confucian moral vision, good. Nonetheless, in both popular discourse and in much the secondary literature, the doctrine is characterized in terms of a moral ‘ought’. We will adopt this perspective, and talk of the ‘filial duty of care’. We investigate the empirical question of whether Chinese communities still have a strong sense of this duty. We conclude that although there is a widespread perception among Chinese communities that their sense of filial duty of care has been eroded, in fact the adherence to it remains robust.